Executive Functioning in Chinese Patients With Obsessive Compulsive Disorder - Ren, Huicong; Li, Haibin; Huang, Jin; Zhang, Nan; Chen, Ruiqin; Liu, Wenjuan; Zhang, Zhaohui; Zhang, Chencheng (Frontiers in Psychiatry, 2021)
Introduction: Studies have shown that patients with obsessive compulsive disorder (OCD) often perform more poorly than healthy control (HC) participants on cognitive tasks involving executive functions. Most studies, however, have been performed in Western countries and societies, making it uncertain whether impaired executive functions can also be observed among non-Western patients with OCD. To address this gap in the literature, we evaluated several executive functions in Chinese patients with OCD and HCs. Methods: Participants included consisted of 46 Chinese patients with OCD (25 men, 21 women), ranging in age from 19 to 56 years, and 45 matched HCs without any self-reported lifetime psychiatric disorder. They all lived in Shanghai or the surrounding area. Five tests of the Cambridge Neuropsychological Test Automated Battery (CANTAB) were used to evaluate several executive functions (response inhibition, spatial working memory, planning, and cognitive flexibility) along with testing basic learning and visual recognition memory. Statistical tests using a Bonferroni-corrected significance level of p = 0.003 were performed to assess overall patient-control group differences in cognitive performance. Additionally, we explored performance differences between patients classified as having either relatively mild symptoms or severe symptoms based on the individual total scores on the Yale-Brown Obsessive-Compulsive Scale. Results: There were no significant performance differences between patients with OCD and HC in any of the cognitive tests. Similarly, cognitive performance of patients with relatively mild OCD symptoms did not differ significantly from that of patients with severe symptoms. Conclusions: These results do not seem to support the view that impaired executive functioning represents a basic cognitive and pathophysiological feature of Chinese patients with OCD. However, due to study limitations, additional research is required before this conclusion can be well accepted.